Effects of heat and high-pressure treatments on the solubility and immunoreactivity of almond proteins. (15th May 2016) - Zhang, Yan; Zhang, Jieqiong; Sheng, Wei; Wang, Shuo; Fu, Tong-Jen
Highlights: Processing effects on almond extracts were studied under dry and wet conditions. In synergy, water, heat and pressure reduced immunoreactivity of almond proteins. The long term goal of the research is to reduce the allergenicity of almond. Abstract: The effects of dry and moist heat, autoclave sterilization and high-pressure treatment on the biochemical characteristics and immunological properties of almond proteins were investigated. Changes in the solubility and immunoreactivity of almond proteins extracted from treated almond flour were evaluated using a total protein assay, indirect competitive inhibition enzyme-linked immunosorbent assay (IC-ELISA), and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE). Almond proteins were stable during dry-heat treatment at temperatures below 250 °C. Dry heat at 400 °C, boiling, autoclave sterilization and high-pressure treatment in the presence of water at ⩾500 MPa greatly reduced the solubility and immunoreactivity of almond proteins. SDS–PAGE revealed that the protein profiles of almond flour samples treated under these conditions also changed significantly. The synergistic effects of heat, pressure and the presence of water contributed to significant changes in solubility and immunoreactivity of almond proteins.